Quantum-limited heat conduction over macroscopic distances - Partanen, Matti (Nat Phys, 2016)
The emerging quantum technological apparatuses1, 2, such as the quantum computer3–6, call for extreme performance in thermal engineering7. Cold distant heat sinks are needed for the quantized electric degrees of freedom due to the increasing packaging density and heat dissipation. Importantly, quantum mechanics sets a fundamental upper limit for the flow of information and heat, which is quantified by the quantum of thermal conductance8–10. However, the short distance between the heat-exchanging bodies in the previous experiments11–14 hinders their applicability in quantum technology. Here, we present experimental observations of quantum-limited heat conduction over macroscopic distances extending to a metre. We achieved this improvement of four orders of magnitude in the distance by utilizing microwave photons travelling in superconducting transmission lines. Thus, it seems that quantum-limited heat conduction has no fundamental distance cutoff. This work establishes the integration of normal-metal components into the framework of circuit quantum electrodynamics15–17 which provides a basis for the superconducting quantum computer18–21. Especially, our results facilitate remote cooling of nanoelectronic devices using far-away in-situ-tunable heat sinks22, 23. Furthermore, quantum-limited heat conduction is important in contemporary thermodynamics24, 25. Here, the long distance may lead to ultimately efficient mesoscopic heat engines with promising practical applications26.